(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Judicial activism has played a pivotal role in shaping the legal landscape of modern India. It refers to the proactive role taken by the judiciary, particularly the higher courts, in not only interpreting laws but also filling legislative or executive voids by passing progressive judgments. Rooted in the principle of judicial review, judicial activism aims to ensure that justice is not denied by governmental inaction or legislative shortcomings. In India, the judiciary has often been lauded as the protector of the Constitution, stepping in when the executive or legislative branches fail to uphold fundamental rights or protect the rule of law. Since the adoption of the Constitution in 1950, India has witnessed numerous instances where the judiciary has extended its role beyond traditional boundaries, addressing socio-economic issues, environmental concerns, and human rights violations. The Supreme Court of India has often invoked Articles 32 and 142 of the Constitution to deliver landmark judgments that have redefined the scope of justice, equality, and governance.